Preliminary results on the photo-transferred thermoluminescence from Ge-doped SiO 2 optical fiber - Zulkepely, N.N.; Amin, Y.M.; Nor, R.M.; Bradley, D.A.; Maah, M.J.; Mat Nawi, S.N.; Wahib, N.F. (Elsevier, 2015)
A study is made of photo-transferred thermoluminescence (PTTL), the TL being induced by transferring charge carriers from deeper to more superficial traps through energetic light exposure. Potential applications include dose reassessment in radiation dosimetry and also as a useful tool for dating. With incomplete emptying of deep traps following first readout, subsequent UV exposure is shown to lead to charge transfer to more shallow traps. Using Ge-doped SiO2 optical fibers exposed to 60Co gamma rays, the PTTL from the medium has been characterized in terms of the stimulation provided by exposure to a UV lamp and duration of exposure, maximum read-out temperature and pre-gamma irradiation dose. Ge-doped SiO2 optical fibers of flat cross-sectional shape have been used in this study. The efficiency of dose reassessment was compared to that of the highly popular phosphor-based TL detector TLD-100. Results show the maximum temperature of readout to have no measurable effect on the PTTL signal. For doses from 20 to 500cGy, the method is shown to be effective using a UV lamp of wavelength 254nm, also being indicative of potential application for doses on either side of the range currently investigated. A study was also made of the effect of UV exposure time on PTTL, seeking to determine the greatest accessible sensitivity and lowest measurable dose.